Legal Aspects of Tackling the Crime of Trafficking in Persons from the Perspective of Criminology - Ameilia Putri Syavei, Amanda; Putri, Alicia Dwi; Maulana, M Fajar; Sutrisno, Endang; Dikrurrahman, Diky (Jurnal Sosial Teknologi, 2024)
The current cases of trafficking in persons seen from the many news reports in social media and print media show how much special attention is needed regarding the crime of trafficking in persons. This research uses a qualitative method. We conducted this research at the Cirebon Regency Police, the Sumber District Court, the Sumber District Attorney's Office, and at several law firms to process data regarding victims of human trafficking crimes that occurred in Cirebon Regency, so that we can find out what factors can become a victim of human trafficking. The victim's own involvement in what happened because of various activities such as recruiting, transporting, and hiding someone for exploitation, including sexual, forced labor, or slavery. Conflict and violence in society also exacerbate this condition, forcing people to seek a better life. Efforts to protect victims of human trafficking have been provided, including various elements of legal protection including being listed in the law, providing physical and psychological assistance, international cooperation and prevention which are considered to reduce the risk for people to become victims of human trafficking. Victim protection, including.